2023
DOI: 10.5194/amt-16-2353-2023
|View full text |Cite
|
Sign up to set email alerts
|

DeLiAn – a growing collection of depolarization ratio, lidar ratio and Ångström exponent for different aerosol types and mixtures from ground-based lidar observations

Athena Augusta Floutsi,
Holger Baars,
Ronny Engelmann
et al.

Abstract: Abstract. This paper presents a collection of lidar-derived aerosol intensive optical properties for several aerosol types, namely the particle linear depolarization ratio, the extinction-to-backscatter ratio (lidar ratio) and the Ångström exponent. The data collection, named DeLiAn, is based on globally distributed, long-term, ground-based, multiwavelength, Raman and polarization lidar measurements, conducted mainly with lidars that have been developed at the Leibniz Institute for Tropospheric Research. The i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 129 publications
3
14
1
Order By: Relevance
“…The corresponding mean values are summarized in Table 1. In the lofted layer, the mean lidar ratio between 1.3 and 5.3 km of 58.4 and 47.3 sr (at 355 and 532 nm) and the particle linear depolarization ratio of 24.5, 28.1 and 24.1 % (at 355, 532 and 1064 nm) are in a typical range for desert dust (Haarig et al, 2017;Floutsi et al, 2023). In the PBL, relatively clean marine conditions (Bohlmann et al, 2018) were observed, which were characterized by a mean lidar ratio of 17.4 and 23.7 sr (at 355 and 532 nm) between 0.25 and 0.6 km and a mean particle linear depolarization ratio of 0.7, 1.1 and 1.0 % (at 355, 532 and 1064 nm) between 0.06 and 0.6 km.…”
Section: Reference Case (16 September 2021)mentioning
confidence: 97%
“…The corresponding mean values are summarized in Table 1. In the lofted layer, the mean lidar ratio between 1.3 and 5.3 km of 58.4 and 47.3 sr (at 355 and 532 nm) and the particle linear depolarization ratio of 24.5, 28.1 and 24.1 % (at 355, 532 and 1064 nm) are in a typical range for desert dust (Haarig et al, 2017;Floutsi et al, 2023). In the PBL, relatively clean marine conditions (Bohlmann et al, 2018) were observed, which were characterized by a mean lidar ratio of 17.4 and 23.7 sr (at 355 and 532 nm) between 0.25 and 0.6 km and a mean particle linear depolarization ratio of 0.7, 1.1 and 1.0 % (at 355, 532 and 1064 nm) between 0.06 and 0.6 km.…”
Section: Reference Case (16 September 2021)mentioning
confidence: 97%
“…Recently, quality-controled 20-year climatological datasets were released. These datasets have been widely used to identify aerosol types and respective optical properties (Papagiannopoulos et al, 2018), infer microphysical properties through inversion techniques (Müller et al, 2016), increase optical information through lidar/photometer synergies (Chaikovsky et al, 2016), study aerosol hygroscopicity (Bedoya-Velásquez et al, 2018) and aerosol-cloud interactions (Mamouri and Ansmann, 2017;Marinou et al, 2019), optimize satellite product retrievals (Amiridis et al, 2013;Nicolae et al, 2018;Floutsi et al, 2023) e. ACTRIS as a tool for monitoring extreme events and atmospheric hazards ACTRIS data have been widely used to characterize specific or extreme events affecting the atmosphere either caused by natural or human-induced phenomena. The capacity to be operational 24/7 at most of the Observational Platforms has been essential on many occasions over the past decade.…”
Section: B) Contribution Of Actris To the Understanding Of Atmospheri...mentioning
confidence: 99%
“…DeLiAn (Depolarization ratio, Lidar ratio, and Ångström exponent) is a newly developed dataset providing aerosol-speciated properties acquired using ground-based lidars operated in experimental campaigns (e.g., SAMUM 1/2, SALTRACE) or contribute to networks (e.g., EARLINET) [67,70,71,74,[108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127]. Ship-borne vertically resolved aerosol measurements in the Atlantic Ocean have been also obtained using Lidars mounted on the Meteor and the Polastern research vessels [72,[128][129][130][131].…”
Section: Delianmentioning
confidence: 99%
“…The separation of the aerosol load on its counterparts within a layer is made according to Equation ( 5) by setting depolarization ratios equal to 0.28 and 0.03 for the dust (δ d ) and non-dust components (δ nd ), respectively. The depolarization values have been extracted from the DeLiAn dataset [74]. Based on Equation ( 5), the dust backscatter coefficient (β d ) is obtained, contributing to the total measured amount (β p ), whereas the portion of the backscattered signal attributed to nondust particles is calculated via the subtraction of these two terms (Equation ( 6)).…”
Section: Separation Of Dust and Non-dust Components In Dusty Mixturesmentioning
confidence: 99%
See 1 more Smart Citation